Mediating effect of e-service quality perceptions on attitude and trust toward online shopping - Al-Nasser, Mohammad; Yusoff, Rushami Zien; Islam, Rabiul; Zainal Abidin, Irwan Shah; Samsudin, Shamzaeffa (Medwell Journals, 2016)
Attitude is referred to as a positive or negative evaluation of people, activities, ideas, objects, event or just about anything in the environment. Trust is significant for the success of online consumer purchasing.In addition, it was revealed that trusting beliefs affect positively online shopping intentions.The aim of the study is to determine the mediating effect of e-Service quality perceptions on trust and attitude toward online shopping.A quantitative research design was adopted to collect data. Multiple regression analysis method was used to conduct this study. The findings of the study will contribute to both theory and practice.The results of this study have important contributions and implications for practitioners and policy-makers.This study contributed to the field of e-Service quality perceptions on consumers’ trust and attitude relationship with online shopping in the context of developing countries.It is hoped that e-Service quality constitutes drivers of trust which consequently influence online purchase attitude and on the service quality consumer expectations in both Malaysia and Saudi Arabia.The effect of service quality perception on trust is lower for consumers having high-risk perception while the effect is higher for those with low risk perception.